Mitochondrial dysfunction drives a neuronal exhaustion phenotype in methylmalonic aciduria - Matthew C. S. Denley; Monique S. Straub; Giulio Marcionelli; Miriam A. Güra; David Penton; Igor Delvendahl; Martin Poms; Beata Vekeriotaite; Sarah Cherkaoui; Federica Conte; Ferdinand von Meyenn; D. Sean Froese; et al. (Communications Biology)
Abstract Methylmalonic aciduria (MMA) is an inborn error of metabolism resulting in loss of function of the enzyme methylmalonyl-CoA mutase (MMUT). Despite acute and persistent neurological symptoms, the pathogenesis of MMA in the central nervous system is poorly understood, which has contributed to a dearth of effective brain specific treatments. Here we utilised patient-derived induced pluripotent stem cells and in vitro differentiation to generate a human neuronal model of MMA. We reveal strong evidence of mitochondrial dysfunction caused by deficiency of MMUT in patient neurons. By employing patch-clamp electrophysiology, targeted metabolomics, and bulk transcriptomics, we expose an altered state of excitability, which is exacerbated by application of dimethyl-2-oxoglutarate, and we suggest may be connected to metabolic rewiring. Our work provides first evidence of mitochondrial driven neuronal dysfunction in MMA, which through our comprehensive characterisation of this paradigmatic model, enables first steps to identifying effective therapies.